Single best answers and EMQs in clinical pathology - Dubb, Sukhpreet Singh (CRC Press, Taylor & Francis Group, 2013)
This book presents 200 SBA-style and 50 EMQ-style questions arranged by sub-specialty area as well as a practice exam of random questions. A clear discussion of how the correct answer was reached and other options ruled out for every question is given at the end of each section, making this book an excellent learning aid during all stages of undergraduate clinical studies and beyond into postgraduate training, and particularly while preparing for medical finals.